The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Poland. (4th May 2017) - Klimczak, Karol Marek; Krasodomska, Joanna
ABSTRACT: We outline the process of implementation of the accounting Directive 2013/34/EU by the Republic of Poland in the context of references to IFRS. The purpose of the article is to determine to what extent IFRS are used by actors taking part in the legislative and enforcement processes. The accounting regulation in Poland comprises an act of Parliament and the regulations of the Ministry of Finance. As a result the regulation is relatively succinct and many elements present in IFRS are not covered, while the issues of record-keeping and verification of accounting documentation receive more attention. A review of the responses to a call for opinions reveals that IFRS are rarely mentioned.